Microstructural Evolution during Homogenization and Hot Deformation for As‐Cast H13 Steel. Issue 3 (18th December 2020) - Han, Yahui; Li, Changsheng; Ren, Jinyi; Qiu, Chunlin; Li, En; Chen, Shuaishuai
Abstract : The hot compression experiments are accomplished to investigate the microstructural evolution of as‐cast H13 steel during homogenization treatment and hot deformation. At a certain homogenization temperature, the dynamic recrystallization (DRX) volume fraction increases with increasing strain and deformation temperature and decreasing strain rate. However, the DRX is also easy to proceed at a high strain rate of 5 s −1 due to the high shear stress. The recrystallization is inhibited in a dendrite segregation region. The residual dendrite segregation left after homogenization treatment will improve the recrystallization nucleation rate during the subsequent deformation. The recrystallization grains preferentially nucleate in the dendrite region, and the grain growth is inhibited by the dendrite segregation. The partial homogenization before deformation is beneficial to achieve the fine microstructure. Abstract : There exists the extensive dendrite segregation in as‐cast H13 steel. After partial homogenization, the recrystallized grains prefer to nucleate in the dendrite region, and the enriched alloying atoms and carbide particles in the dendrite segregation region will obviously inhibit the recrystallization grain growth. The partial homogenization before hot deformation is beneficial to achieve the fine microstructure.